Power shifts in international organisations: China at the United Nations - Sebastian Haug; Rosemary Foot; Max-Otto Baumann (Global Policy, 2024)
The People's Republic of China is central to current debates about power shifts in international organisations, but a systematic and comprehensive assessment of China-related shifts has been missing. As Special Issue introduction, this article contributes to addressing this gap and examines whether, how and to what extent China-related power shifts have unfolded at the United Nations (UN) over the last two decades or so. We define power shifts as changes in the ability of actors to shape others' capacities to act and outline a framework that builds on Barnett and Duvall's four power types of compulsory, institutional, structural and productive power. Drawing from Special Issue contributions, our analysis covers empirical insights from the UN's three main pillars – peace and security, development and human rights – and paints an uneven picture. Despite continuing Western dominance, China is mobilising more compulsory power means than two decades ago. Chinese attempts to enact institutional power have also increased but mostly unfold in multilateral niches and remain cautious. While China's structural power position has expanded, China-related effects in productive power have so far remained limited and scattered. We conclude with a combined assessment of changes across power types and discuss research and policy implications.
Keywords: 320